Momentum transfer from Arc to slag bath in an ilmenite smelting DC Arc furnace - a computational analysis - Makgoale, Tumelo (Stellenbosch : Stellenbosch University, 2021)
Thesis (MEng)--Stellenbosch University, 2021.